2001
DOI: 10.1073/pnas.231313998
|View full text |Cite
|
Sign up to set email alerts
|

Point mutation in the mouse glucocorticoid receptor preventing DNA binding impairs spatial memory

Abstract: Activation of central glucocorticoid receptors caused by the stress that is associated with a learning task facilitates storage of the acquired information. The molecular mechanism underlying this phenomenon is entirely unknown. Glucocorticoid receptors can influence transcription both through DNA binding-dependent and -independent mechanisms. To assess the importance of these two modes of action for spatial memory, we here used male mutant mice in which homodimerization and DNA binding of the glucocorticoid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
147
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 262 publications
(160 citation statements)
references
References 24 publications
11
147
0
2
Order By: Relevance
“…[79][80][81] Decreased expression or binding capacity of the hippocampal GR is known to result in impaired spatial learning. [82][83][84] However, we did not find an effect of FAE on hippocampal GR expression, which is in agreement with a previous report. 85 Fetal overexposure to endogenous glucocorticoids, such that occurs after reducing the activity of the 11b-hydroxysteroid dehydrogenase type 2 (11b-HSD2), the 'barrier' enzyme to maternal steroids that rapidly inactivates glucocorticoids in placenta and many fetal tissues, affects neuroendocrine and behavioral responses of the adult offspring.…”
Section: Effects Of Prenatal Alcohol Exposure On Behavior and Gene Exsupporting
confidence: 93%
“…[79][80][81] Decreased expression or binding capacity of the hippocampal GR is known to result in impaired spatial learning. [82][83][84] However, we did not find an effect of FAE on hippocampal GR expression, which is in agreement with a previous report. 85 Fetal overexposure to endogenous glucocorticoids, such that occurs after reducing the activity of the 11b-hydroxysteroid dehydrogenase type 2 (11b-HSD2), the 'barrier' enzyme to maternal steroids that rapidly inactivates glucocorticoids in placenta and many fetal tissues, affects neuroendocrine and behavioral responses of the adult offspring.…”
Section: Effects Of Prenatal Alcohol Exposure On Behavior and Gene Exsupporting
confidence: 93%
“…By contrast, metyrapone had no effect on synaptic GluA1 expression (data not shown). To investigate the involvement of GR receptorsFwhich mediate corticosterone actions and were shown to be essential for consolidation of long-term spatial memory (Oitzl et al, 2001)Fwe injected the GR antagonist RU38486 before training and found that it inhibited the increase in GluA2 observed in 221C-trained mice (Figure 3e; RU vs Ctrl po0.05). Corticosterone injections (10 mg/kg; i.p.)…”
Section: Blockade Of Stressful Learning-elicited Corticosterone Releamentioning
confidence: 99%
“…These mice have normal hypothalamic CRH expression, increased pituitary proopiomelanocortin (POMC) expression, normal plasma ACTH levels, and increased plasma corticosterone levels. They also exhibit impaired spatial memory but normal anxiety-like behavior [38]. Mice that overexpress the glucocorticoid receptor (YGR mice) have a marked decrease in hypothalamic CRH and pituitary POMC expression, increased plasma ACTH levels, and decreased plasma corticosterone levels [39].…”
Section: Modulation By Mineralocorticoid and Glucocorticoid Receptorsmentioning
confidence: 99%